Recent progress in tsunami deposit investigations in Taiwan - Neng-Ti Yu; Jiun-Yee Yen; Shyh-Jeng Chyi; Cheng-Hao Lu; Nobuhisa Matta Matsuta; I-Chin Yen (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract Identifying deposits of modern/historical and prehistorical tsunamis in Taiwan has been successful in the past two decades and has substantially increased the extant tsunami catalogs, which have been limited in the past four centuries due to scarce and ambiguous historical accounts. In this review, the initiation of the investigation is briefly discussed, partly in response to the latest catastrophic tsunamis in the Indo-Pacific and the stimulated public concern in Taiwan. Major developments and results of the investigation include the onset of the first stage before 2010, with findings in Keelung, the eastern coast, and Lanyu Island, and the second/ongoing stage after 2013, with findings in the northern and eastern coasts and Penghu Islands. These findings contributed to validating the debated historical events, expanding the event number and time span of the tsunami catalog, and elaborating on tsunami processes, which collectively enabled the delineation of the recurrence time intervals between events. Limitations, uncertainty, further contributions, and feedback are discussed including insights into the regional western Pacific hazards of tsunamis, earthquakes, and volcanic eruptions; the principles of recognizing tsunami deposits and processes; and the propositions of future studies and hazard mitigations in Taiwan.